When to invest in carbon capture and storage: A perspective of supply chain. (September 2018) - Wang, Xiping; Qie, Shaoyuan
Highlights: Study the optimal investment timing in CCS from the perspective of supply chain. Present analytical models for CCS investment under different scenarios. A dual-echelon supply chain requires a higher threshold than that of base case. Abstract: The purpose of this study is to investigate the investment threshold of carbon capture and storage (CCS) project from the perspective of supply chain, overcoming the limitations of previous works regarding this topic mainly from a single investor's perspective. An analytical real options model was firstly presented for the scenario of centralized decision making, then the model was extended by integrating the real options theory with the game theory to examine the CCS investment threshold for the scenario of dual-echelon supply chain. An interesting finding is that CCS investment requires a much higher threshold under the dual-echelon supply chain than that under the centralized scenario, and this finding is consolidated by a numerical example simulation. Furthermore, the results of the numerical simulation indicated that the CCS investment threshold is positively affected by carbon price volatility, CO2 capture rate and the transfer payments coefficients, while negatively affected by capital subsidy. These conclusions can provide theoretical foundation for decision-making of CCS investment and related policy-making.